Penerapan Etika Perawat Dalam Pelayanan Praktik Home Care - Arinda Cahyani; Karisma Adiya Putri; Risma Ayu Putri Diani; Putri Sovia Melati (Pusat Unggulan IPTEK, Poltekkes Kemenkes Palembang, 2022)
Nurses in providing nursing services must always uphold the code of nursing ethics as a form of responsibility both to patients, their responsibilities to colleagues or other professions, as well as their responsibilities to their professional organizations (PPNI). This study aims to determine the form of application of the code of ethics from the aspect of responsibility for nursing services both to patients, colleagues or other professions as well as to professional organizations. This study uses a descriptive method with a quantitative approach to Nursing Services in Homecare. The results drawn from this study are that nurse services have referred to responsibilities and there are no violations in Nursing Ethics so that there is no effect on Nursing Services.